Sciatica-like pain caused by cervical spondylotic myelopathy: four case reports and systematic review - Han, Changsheng; Wang, Jingming; Wang, Lei; Gong, Qinglei; Huang, Weimin (Frontiers in Medicine, 2024)
Objective This study aimed to demonstrate and characterize a rare cervical spondylotic myelopathy (CSM) with sciatica-like pain as the main clinical manifestation through case presentation and systematic review. Methods Four cases of CSM with sciatica-like pain as the main clinical manifestation were retrospectively studied. A systematic review of electronic databases such as PubMed, Embase, and Web of Science was conducted to explore the clinical characteristics of CSM with sciatica. Results All four cases of CSM symptomatic of sciatica-like pain were initially diagnosed with lumbar degenerative conditions. However, due to the presence of neurological signs such as hyperactive tendon reflexes, a positive Babinski sign, or a Hoffmann sign, they underwent further cervical MRI scans. Eventually, all four cases were diagnosed with CSM and experienced relief from sciatica after cervical decompression surgery. The systematic review analyzed a total of four studies with a combined sample size of 10 cases, all of whom experienced a reduction in sciatica-like pain following cervical decompression surgery. Conclusion CSM symptomized by sciatica-like pain can often be misdiagnosed as lumbar degenerative disease. Preoperative abnormal neurological signs associated with CSM may aid in diagnosing this condition. In addition, the clinical presentation of hyperextension of the cervical spine resulting in worsening lower limb pain may serve as diagnostic indicators for this disease.